The system, control and cultural management of the Indian diamond firms in countries like Hong Kong and Antwerp compared to India. - Shah, Nirav (2010)
In the era of globalization, internalization of business is at its peak. In order to survive the severe competition from the competitors, the companies expand their business operations across international boundaries. Due to the growing importance of globalization in relation to business context, the need to study the cross-cultural management is very essential. Therefore, various researchers have studied the different aspects of cross-cultural management. However, very little research has been conducted on the cross-cultural differences that are faced by the large organizations. This research aims to study these cultural differences in relation to the diamond industry which is a booming industry with a very vast scale globally. The findings of this study are derived from a qualitative approach as the topic under consideration cannot be quantified. Semi-structured interviews of the owners as well as the employees of the Indian diamond trading companies were conducted in order to gain an insight of the issues faced by them in working cross-culturally. Also, ethnographic research was conducted by the researcher. The findings of the research conducted provide an in-depth knowledge of the major cross-cultural differences faced by the companies or its employees. These findings are then further analyzed in detail and its impact on the business existence is also studied. It also mentions the various ways in which companies or the employee’s can handle the cultural differences and run the business successfully. Different cultural problems can be faced by the Indian companies in other countries like Hong Kong and Antwerp. However, this research attempts to point out few of the main cross-cultural issues faced by these companies.